1977
DOI: 10.1042/bj1670823
|View full text |Cite
|
Sign up to set email alerts
|

The arrangement of substrate and organophosphorus-inhibitor leaving groups in acetylcholinesterase active site

Abstract: The leaving groups of serine esterase substrates and organophosphorus inhibitors bind to different loci at the enzyme active site. Kinetic proof of this general conclusion is presented in the case of acetylcholinesterase reactions. The proposed model for acetylcholinesterase active site provides a new stereochemical mechanism for the phosphorylated enzyme reactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Debord et al [37] showed that the (O)PN 3 moeity in aliphatic phosphoramides interacts with the hydrophilic zone of the catalytic site of butyrylcholinesterase. Jarv et al indicated [38] that in acetylcholinesterase three hydrophobic regions bind to hydrocarbon substituents and surround this zone. In phosphoramide 2, the existence of two nitroaniline groups decrease the lipophilicity of the aromatic ring.…”
Section: Discussionmentioning
confidence: 99%
“…Debord et al [37] showed that the (O)PN 3 moeity in aliphatic phosphoramides interacts with the hydrophilic zone of the catalytic site of butyrylcholinesterase. Jarv et al indicated [38] that in acetylcholinesterase three hydrophobic regions bind to hydrocarbon substituents and surround this zone. In phosphoramide 2, the existence of two nitroaniline groups decrease the lipophilicity of the aromatic ring.…”
Section: Discussionmentioning
confidence: 99%
“…Because the geometry of nucleophilic attack at a carbonyl carbon atom (present in the substrate and in carbamates) differs from that of nucleophilic attack at a tetrahedral phosphorus atom, Järv, J. et al (1977) took the view that, if the serine OH were to be relatively fixed, it would not be possible for the leaving groups in these molecules to occupy the same region of the enzyme active site. These authors compared data on the rate of enzyme-catalysed hydrolysis of acetate esters (CH3COOR, where R is a simple alkyl group) with results for the rate of reaction with analogous phosphonates (RO) (CH 3 ) P(0)(SC 4 H 9 ).…”
Section: And Carbamatesmentioning
confidence: 99%
“…However the question of what is the binding site of the remote group of an organophosphorus inhibitor at the active center of ACE is still under discussion. In particular, it was demonstrated [19] that substituents R in the molecules ofsubstrates CH3C(O)OR and ACE inhibitors (RO)CH3P(O)SC4H 9 interact with the same locus Pl in the active center of the enzyme (see scheme in Fig. 5), so that the remote group of the inhibitor (in this vase SC4H9) is bound at the locus P3 of the active center of ACE, rather than at the anionic site.…”
mentioning
confidence: 98%
“…This result suggests that a high activity of the compounds is provided by electronegative substituents, which implies that the active center of the enzyme must contain groups capable of retaining these electronegative fragments. [19]; P i and P2 are the regions of binding of the remote group X and the awl part of the substrate, respectively; P3 is the region of binding the remote group X of the organophosphorus inhibitor.…”
mentioning
confidence: 99%